2018
DOI: 10.1038/s41598-018-22205-z
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature 90° phase-matching in zirconium and magnesium co-doped lithium niobate crystals

Abstract: Laser has been widely used in many aspects, by now it is difficult to get each frequency that we want, and frequency conversion is an effective way to obtain different frequency laser through a nonlinear optical crystal. MgO-doped LiNbO3 (Mg:LN) crystal has usually been used for second harmonic generation (SHG) through temperature-matching configuration with a stove, till now a room temperature 90° phase-matching is still lacking. Here we find that the SHG of Nd:YAG laser is achieved at 26.1 °C while the optic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 44 publications
2
5
0
Order By: Relevance
“…We can derive from these data that MgO doping further reduces the refractive index change of crystals, while its effect is similar to that of the single optical damage resistant dopant. In addition, note that the 3.0 mol % MgO and 1.5 mol % ZrO2 co-doped LiNbO3 has almost the same optical damage resistance as the previously reported 5.0 mol % MgO and 1.7 mol % ZrO2 co-doped LiNbO3 [14].…”
Section: The Temperature For 90 • Phase Matchingsupporting
confidence: 81%
See 2 more Smart Citations
“…We can derive from these data that MgO doping further reduces the refractive index change of crystals, while its effect is similar to that of the single optical damage resistant dopant. In addition, note that the 3.0 mol % MgO and 1.5 mol % ZrO2 co-doped LiNbO3 has almost the same optical damage resistance as the previously reported 5.0 mol % MgO and 1.7 mol % ZrO2 co-doped LiNbO3 [14].…”
Section: The Temperature For 90 • Phase Matchingsupporting
confidence: 81%
“…Figure 4 describes the phase-matching temperature of LN:Zr,Mg as a function of the mole fraction of MgO doping in the melt. Moreover, to clearly elucidate the dependence between the phase-matching temperature and the MgO doping concentration, we also added the measured phase-matching temperature for the 1.5 mol % ZrO 2 and 5.0 mol % MgO co-doped LiNbO 3 crystal (labeled as LN:Zr,Mg 5.0 ), as reported in our published paper [14]. As shown in the figure, the phase-matching temperature increases with increased MgO doping concentration, and the phase-matching temperature follows a linear function of the mole fraction of MgO doping in the melt.…”
Section: The Temperature For 90 • Phase Matchingmentioning
confidence: 99%
See 1 more Smart Citation
“…For comparison, the 2.0 mol.% ZrO 2 -doped congruent LN crystal was also prepared, labeled as LN:Zr 2.0 . Here, the crystal growth and treatment had been described in our previous report [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Besides, Zr doping also improves the near infrared emission efficiency in LN:Er, LN:Yb,Er crystals [ 17 ]; meanwhile, it can also stabilize the signal output of the Ti-diffused LN waveguides under the high-power pumping without optical damage observed [ 18 ]. Furthermore, we have reported that some additional ZrO 2 doping into LN:Mg not only can finely adjust the phase-matching temperature but also realize the room temperature noncritical phase-matching [ 19 ]. The above research results suggest that Zr doping have such a strong impact on the properties of LN, so further research on its influence on the UV photorefraction of LN:Mg is very necessary and meaningful to promote the laser frequency conversion to UV wavelength region.…”
Section: Introductionmentioning
confidence: 99%